2019
DOI: 10.1002/aelm.201901174
|View full text |Cite
|
Sign up to set email alerts
|

Thin, Skin‐Integrated, Stretchable Triboelectric Nanogenerators for Tactile Sensing

Abstract: a trend. [22-27] Currently, self-powered technologies based on piezoelectric materials [28-32] and triboelectric nanogenerator [33-37] are two typical strategies to convert mechanical energy into electricity. Compared to piezoelectric nanogenerator, triboelectric nanogenerator is more suitable for energy harvesting, as it typically can provide much higher output voltage and current. [38-40] However, reports of using triboelectric nanogenerator for flexible sensors are still much less than those of piezoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 55 publications
1
54
0
Order By: Relevance
“…In Fig. 3a, Liu et al reported self-powered epidermal electronics with a tactile sensing function 84 . This kind of epidermal electronics can reflect the pressure on the skin, as well as the pressure distribution, through the triboelectric signal, which is of broad potential interest in wearable electronics.…”
Section: Portable and Wearable Self-powered Sensing Systemmentioning
confidence: 99%
“…In Fig. 3a, Liu et al reported self-powered epidermal electronics with a tactile sensing function 84 . This kind of epidermal electronics can reflect the pressure on the skin, as well as the pressure distribution, through the triboelectric signal, which is of broad potential interest in wearable electronics.…”
Section: Portable and Wearable Self-powered Sensing Systemmentioning
confidence: 99%
“…[98][99][100][101] Owing to various advantages of TENG, such as a broad range of material selection, simplicity of structure design, cost-effectiveness, and high output, TENG has been intensively explored in the application of flexible power sources and self-powered environmental sensors, which exhibits the great potential for the future development of wearable electronics and the Internet of Things. [102][103][104][105] 3.1 | Operating mechanisms of triboelectricity Figure 5A demonstrates the construction of the first flexible TENG with vertical contact-separation (CS) mode. 88 The basic working principle of TENG is through a conjunction of triboelectrification and electrostatic induction, which is illustrated in Figure 5B in detail.…”
Section: Flexible Tengmentioning
confidence: 99%
“…Since 2012, the invention of TENG has made full utilization of this effect, converting mechanical energy in the ambient environment into electricity, such as vibrations, wind, water waves, and human motions . Owing to various advantages of TENG, such as a broad range of material selection, simplicity of structure design, cost‐effectiveness, and high output, TENG has been intensively explored in the application of flexible power sources and self‐powered environmental sensors, which exhibits the great potential for the future development of wearable electronics and the Internet of Things …”
Section: Flexible Tengmentioning
confidence: 99%
“…In particular, tactile sensors capable of transducing physical touch to electrical signals have demonstrated their practical application in human health monitoring, security monitoring, and artificial intelligence [9][10][11][12][13][14][15] based on different transduction mechanisms, including capacitance [16][17][18] , piezoresistivity [19][20][21] , and piezoelectricity 22,23 . Owing to the advantages of high sensitivity, low cost, diverse material selection, and zero power consumption, another type of sensor based on a triboelectric nanogenerator (TENG), with the sensing mechanism of coupling triboelectrification [24][25][26][27] and electrostatic induction 28 , has aroused great interest among researchers [29][30][31][32] . For example, Wang et al 31 reported a self-powered triboelectric sensor matrix composed of polydimethylsiloxane (PDMS) as an electrification layer and patterned Ag electrodes serving as chargesensing components and circuit connections.…”
Section: Introductionmentioning
confidence: 99%